Incidental screening of descending colon carcinoma by 18F-FDG PET/MR imaging in a patient with endometrial carcinoma: A case report of Lynch syndrome - Li, Xiaoran; Zhang, Xian; Cui, Bixiao; Ma, Jie; Wang, Shijun; Lu, Jie (Frontiers in Oncology, 2023)
Background Lynch syndrome (LS) is associated with the early onset of carcinoma and the development of numerous types of carcinoma, particularly endometrial and colon carcinomas. LS-associated endometrial carcinoma (EC) has been widely noted by gynecologists. However, there is still a lack of a non-invasive and reliable tool for early screening for LS in patients with EC. There are a few reports of PET and MR images revealing EC associated with LS. Case presentation A 63-year-old female patient presented with postmenopausal intermittent vaginal bleeding. Transvaginal ultrasonography showed a small amount of bleeding in the uterine cavity and no thickening of the endometrium. The levels of relevant tumor markers were all within normal ranges. The endometrial cytology examination hint to possible endometrial adenocarcinoma. The hybrid 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/magnetic resonance (PET/MR) images showed a polypoid mass in the lower uterine segment and unexpectedly found a mass in the descending colon. A colonoscopy confirmed that there was a colon adenocarcinoma in the same place as the PET/MR images. Thus, LS was suspected even though this patient did not match the clinical diagnostic criteria. The gene analysis of both tumors was performed to identify microsatellite instability (MSI) for the diagnosis of Lynch syndrome. Postoperative adjuvant therapy and follow-up protocol customized for patients with Lynch syndrome. Conclusion This case highlights that hybrid 18F-FDG PET/MR imaging could play a key role in the screening for Lynch syndrome in EC patients.